Degradation of automotive materials in palm biodiesel - Fazal, M.A.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (2012)
As compared to petroleum diesel, biodiesel is more corrosive for automotive materials. Studies on the characterization of corrosion products of fuel exposed automotive materials are scarce. Automotive fuel system and engine components are made from different ferrous and non-ferrous materials. The present study aims to investigate the corrosion products of different types of automotive materials such as copper, brass, aluminum and cast iron upon exposure to diesel and palm biodiesel. Changes in fuel properties due to exposure of different materials were also examined. Degradation of metal surface was characterized by digital camera, SEM/EDS and X-ray diffraction (XRD). Fuel properties were examined by measuring TAN (total acid number), density and viscosity. Among the metal investigated, copper is found to be least resistant in biodiesel and formed comparatively more corrosion products than other metals. Upon exposure of metals in biodiesel, TAN number crosses the limit given by standard while density and viscosity remain within the acceptable range of limit. (C) 2012 Elsevier Ltd. All rights reserved.